PENGARUH LATIHAN RESISTANCE BAND TERHADAP KECEPATAN PUKULAN GYAKU-TSUKI PADA ATLET KARATE FIGHTER 50 CLUB - Zaputra, Rayhan; Mariati, Sari; Sari, Suci Nanda; Septri, Septri (Universitas Negeri Padang, 2025)
This study began with the fact that there are still many athletes who are not good at doing gyaku-tsuki punches, there are still many athletes who make mistakes when doing gyaku-tsuki punches. This study aims to see the effect of resistance band training on the speed of gyaku-tsuki punches. This type of research is a pseudo-experiment. The population in this study is all male and female athletes registered at the Figther 50 Club, totaling 15 people. The sample in this study was taken using the propusive sampling technique, namely with certain considerations. Thus, the number of samples in this study is 10 people. The research instrument uses the igyaku-tsuki blow speed test. iStatistical data analysis techniques use the Ililiefors abnormality test and t-test with a significance level of iɑ=0.05. iThe results of this research are that there is an effect of iband irresistance training on igyaku-tsuki hitting speed in iFigther i50 iClub athletes with an average score of i17 in the pretest, and an average score of i25 in the posttest. iThis is proven isignificantly, i.e. after itest i